2009
DOI: 10.1186/bf03352933
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the foreshock of the Earth’s bow shock on the interplanetary shock propagation during their mutual interaction

Abstract: Interplanetary shocks have been recognized as a very efficient source of geomagnetic disturbances. We present a short study of the propagation of one interplanetary (IP) shock observed by five spacecraft located in the solar wind far upstream of the Earth's bow shock as well as in its close vicinity. The IP shock normal was highly inclined from the Sun-Earth line and thus the IP shock-bow shock interaction started at the flank. We have found a significant evolution of IP shock parameters during its motion alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Secondly, the possible deceleration of the solar wind in the foreshock region is only 7-10 km s −1 on average (Bame et al, 1980), indicating an insignificant modification of P d . Thirdly, the reported blurring of the IP shock front in the foreshock region (Prech et al, 2009) was not observed in the present study. Therefore, the foreshock signatures which may substantially vary the input parameters have not been recognized, and the MHD results cannot reveal the foreshock effects.…”
Section: Possible Influences Of the Foreshock Regioncontrasting
confidence: 42%
“…Secondly, the possible deceleration of the solar wind in the foreshock region is only 7-10 km s −1 on average (Bame et al, 1980), indicating an insignificant modification of P d . Thirdly, the reported blurring of the IP shock front in the foreshock region (Prech et al, 2009) was not observed in the present study. Therefore, the foreshock signatures which may substantially vary the input parameters have not been recognized, and the MHD results cannot reveal the foreshock effects.…”
Section: Possible Influences Of the Foreshock Regioncontrasting
confidence: 42%
“…Although this effect would take place within the simulation box, MHD models cannot account for these features. Přech et al (2009) have shown that the IP shock identified near the quasiperpendicular bow shock is seen as a slow and gradual increase of the density and magnetic field strength at the opposite flank. Since IMF was nearly radial, we cannot exclude a modification of the IP shock parameters on its approach to the bow shock.…”
Section: Discussionmentioning
confidence: 96%
“…At the time ACE was located near the Lagrangian point L1, and Wind between L1 and the Earth, while IMP‐8, Geotail, and Interball‐1 were in front of the Earth's bow shock, at dusk‐side, nose, and dawn‐side, respectively (Figure 1). The IP shock passage, which took place between 00:06:29 UT and 00:48:48 UT on August 10, has been previously investigated by Szabo [2005], by Prech et al [2009], and recently by K. Andréeová et al (manuscript in preparation, 2011; hereafter referred to as Andréeová et al, manuscript in preparation, 2011) from points of view other than particle acceleration.…”
Section: Overview Of the Eventmentioning
confidence: 99%